An elderly man with fecal materials in the Foley catheter. Issue 6 (November 2018) - Fang, Pin-Hui; Lin, Wei-Yu; Chang, Ying-Hsin; Hsu, Hsiang-Chin; Lin, Chih-Hao
A 70-year-old man presented to the emergency department with a 2-week history of watery diarrhea. Fecal materials were found in the Foley catheter. A computed tomography of the abdomen and pelvis revealed chronic diverticulitis with enterovesical fistula. The patient was treated with broad-spectrum antibiotics and underwent an urgent surgery with a transverse loop colostomy. The presence of fecaluria should raise the clinical suspicion of enterovesical fistula. Computed tomography is the choice of diagnostic modality.